Phytochemical and Anti-Inflammatory of Uncaria gambir: A Review - Auliana, Fia Rizka; ifora, Ifora; Fauziah, Fitra (Asian Journal of Pharmaceutical Research and Development, 2022)
Inflammation occurs because of a response to tissue injury, cell death, cancer, ischemia, and degeneration. Uncaria gambir is one of the pharmacological solutions in overcoming inflammation. U. gambir has traditionally been used as a febrifuge, pain reliever, anti-inflammatory, antioxidant, and burn wound healing. The purpose of this paper is to present knowledge of the phytochemical and anti-inflammatory properties of U. gambir. This review provides literature evidence from 2011 to 2021. Three search sources were used as literature review sources (Pub Med, Science Direct, and Google Scholar). 13 articles in this review were based on our eligibility criteria. Pharmacological studies reported that U. gambir had been shown to have anti-inflammatory activity by reducing the volume of edema, inhibiting the enzymes COX-1, COX-2, 5-LOX, and iNOS. The phytochemical compounds contained in U. gambir were flavonoids, phenolics, polyphenols, catechins, spiroxylopropane rings, proanthocyanidins, alkaloids, epicatechins, and caffeic acid, which were distributed in leaves, trunk, bark, shoots, stems, and gambir.